An archaeology of institutional confinement : the Hyde Park Barracks, 1848-1886 - Davies, Peter, 1968-; Crook, Penny; Murray, Tim, 1955- (Studies in Australasian historical archaeology, 2013)
The archaeological assemblage from the Hyde Park Barracks is one of the largest, most comprehensive and best preserved collections of artefacts from any 19th-century institution in the world. Concealed for up to 160 years in the cavities between floorboards and ceilings, the assemblage is a unique archaeological record of institutional confinement, especially of women. The underfloor assemblage dates to the period 1848-1886, during which a female Immigration Depot and a Government Assylum for Infirm and Destitute Women occupied the second and third floors of the Barracks. Over the years the women discarded and swept beneath the floors thousands of clothing and textile fragments, tobacco pipes, religious items, sewing equipment, paper scraps and numerous other objects, many of which rarely occur in typical archaeological deposits. These items are presented in detail in this book.